Double-layer composite hydrogel for repairing infectious bone defects and preparation method and application thereof
Patent Information
- Application Number
- CN202611201396.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-08-10
AI Technical Summary
其一为单一功能骨修复材料,如仅具备物理覆盖作用的普通水凝胶或仅促进成骨的磷酸钙骨水泥,功能单一,无法兼顾抗菌与成骨的双重需求
本发明通过功能分区设计,外层水凝胶在植入早期响应近红外光照射产生温和光热效应,快速清除致病菌,控制感染扩散;内层水凝胶持续释放Sr2+,在后期间断促进BMSCs成骨分化、清除活性氧,诱导巨噬细胞向M2型极化,构建抗炎免疫微环境。本发明使得感染性骨缺损修复中的早期抗菌与后期免疫重塑及成骨再生功能在时序上得以衔接,且该双层复合水凝胶具有生物相容性、免疫调控能力及抑菌能力。
Smart Images

Figure CN122701934B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomedical materials technology, specifically to a bilayer composite hydrogel for repairing infected bone defects, its preparation method, and its application. Background Technology
[0002] Infectious bone defects are a major challenge in orthopedic clinics, often accompanied by persistent bacterial infection, inflammatory microenvironment dysregulation, and impaired bone regeneration. Bone repair is a complex, multi-stage, cascading process, from early infection control to later immune microenvironment remodeling, osteogenic differentiation, and bone tissue regeneration, placing comprehensive demands on repair materials in terms of timing, multifunctionality, and synergy. Traditional single-function bone repair materials, such as ordinary hydrogels that only provide physical coverage or calcium phosphate bone cement that only promotes osteogenic growth, are insufficient to simultaneously meet the multi-stage requirements of "early antibacterial action, later immune regulation, and osteogenic growth."
[0003] In related technologies, materials for repairing infected bone defects mainly employ the following categories. First, there are single-function bone repair materials, such as ordinary hydrogels that only provide physical coverage or calcium phosphate bone cement that only promotes osteogenic growth. These have limited functionality and cannot simultaneously meet the dual needs of antibacterial and osteogenic effects. Second, there are composite hydrogels loaded with a single bioactive component. This involves loading a single component, such as an antibacterial agent or growth factor, into an ordinary hydrogel, giving the material a single function of antibacterial or osteogenic effects. However, it is difficult to achieve a temporal synergy between antibacterial and osteogenic functions. Third, there are bilayer or multilayer hydrogels. By constructing a layered structure with functional zones, different bioactive components are distributed within different layers to achieve spatial separation of therapeutic functions. However, existing bilayer hydrogels still suffer from weak interlayer bonding, poor temporal matching of functions, and failure to effectively regulate the bone immune microenvironment (especially guiding macrophages to M2 polarization to promote bone regeneration). Furthermore, they are difficult to adapt to irregular bone defect morphologies.
[0004] However, the above-mentioned methods share the following shortcomings: First, none of them can achieve a sequential, full-cycle repair process of "early antibacterial action, late-stage immune regulation, and osteogenic action," and the antibacterial and osteogenic functions cannot be effectively linked in time. Second, none of them can effectively regulate the local immune microenvironment of infectious bone defects, especially failing to induce macrophages to polarize towards the M2 type to promote bone regeneration. Third, they lack a multifunctional synergistic system that combines highly efficient broad-spectrum antibacterial action, immune microenvironment remodeling, and bone differentiation promotion. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to address the above-mentioned deficiencies in the prior art by providing a bilayer composite hydrogel for the repair of infected bone defects, its preparation method and application. The bilayer composite hydrogel for the repair of infected bone defects, its preparation method and application achieve temporal functional synergy between rapid antibacterial action of the outer layer and continuous osteogenic and immune regulation of the inner layer, as well as full-cycle repair of infected bone defects including early antibacterial action, late-stage immune remodeling and osteogenic regeneration.
[0006] To solve the above problems, the first aspect of the present invention adopts the following technical solution: A method for preparing a bilayer composite hydrogel for repairing infected bone defects includes the following steps: S1, preparation of strontium-based metal-organic frameworks; S2, to prepare sodium alginate oxide; S3, preparation of methacrylamide gelatin; S4, the oxidized sodium alginate, carboxymethyl chitosan and gelatin are mixed, and the strontium-based metal-organic framework is added, and the inner hydrogel is obtained by cross-linking; S5, the sodium alginate oxide, carboxymethyl chitosan, methacrylamide gelatin and copper sulfide nanoparticles are mixed to obtain the outer hydrogel prepolymer solution; S6, the outer layer hydrogel prepolymer is applied to the surface of the inner layer hydrogel, the outer layer is cured by photocrosslinking, and then left to stand to allow interfacial crosslinking to occur between the layers, thus obtaining a bilayer composite hydrogel.
[0007] Furthermore, the strontium-based metal-organic framework is prepared by a hydrothermal reaction of strontium chloride and gallic acid under alkaline conditions.
[0008] Furthermore, the oxidized sodium alginate is prepared by an oxidation reaction between sodium alginate and sodium periodate.
[0009] Furthermore, the methacrylated gelatin is prepared by acylation reaction of gelatin and methacrylic anhydride.
[0010] Further, in step S4, the mass-volume concentrations of sodium alginate, carboxymethyl chitosan, and gelatin are 5% (w / v), 5% (w / v), and 20% (w / v), respectively, and the amount of strontium-based metal-organic framework added is 5 mg / mL.
[0011] Further, in step S5, the mass-volume concentrations of sodium alginate oxide, carboxymethyl chitosan, and methacrylamide gelatin are 5% (w / v), 5% (w / v), and 15% (w / v), respectively; the amount of copper sulfide nanoparticles added is 5 mg / mL; and the outer hydrogel prepolymer also contains 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone.
[0012] Furthermore, in step S6, the photocrosslinking is performed by ultraviolet light irradiation for 5 minutes.
[0013] The second aspect of this invention adopts the following technical solution: A bilayer composite hydrogel for repairing infected bone defects is prepared by a method for preparing bilayer composite hydrogels for repairing infected bone defects.
[0014] The third aspect of this invention adopts the following technical solution: Application of a bilayer composite hydrogel in the preparation of bone defect repair materials, wherein the bone defect is an infected bone defect.
[0015] Furthermore, when the bilayer composite hydrogel is used for bone defect repair, it is combined with near-infrared light irradiation after implantation to stimulate the photothermal antibacterial effect of the outer hydrogel.
[0016] Compared with the prior art, the present invention has the following beneficial effects: This invention employs a functional partitioning design. The outer hydrogel layer responds to near-infrared light irradiation in the early stages of implantation, generating a mild photothermal effect to rapidly eliminate pathogens and control the spread of infection; the inner hydrogel layer continuously releases Sr... 2+ In the later stages, it intermittently promotes osteogenic differentiation of BMSCs, clears reactive oxygen species, induces macrophages to polarize towards the M2 type, and constructs an anti-inflammatory immune microenvironment. This invention enables the early antibacterial function and the later immune remodeling and osteogenic regeneration functions in the repair of infected bone defects to be sequentially connected, and the bilayer composite hydrogel has biocompatibility, immunomodulatory ability and antibacterial ability.
[0017] This invention loads Sr-MOF and CuS nanoparticles onto the inner and outer layers of a hydrogel bilayer, respectively. Sr-MOF not only continuously releases strontium to promote bone formation but also scavenge reactive oxygen species by mimicking the enzyme-like activities of superoxide dismutase and catalase, thus exerting antioxidant and immunomodulatory functions. CuS achieves highly efficient photothermal antibacterial activity under near-infrared light, while simultaneously releasing Cu... 2+ Promoting angiogenesis, the two work synergistically to overcome multiple obstacles to bone repair in infected environments. Meanwhile, the inner layer utilizes Schiff base reactions and molecular entanglement to form a dual-network structure, while the outer layer combines Schiff base reactions and photocrosslinking to give the hydrogel excellent shape adaptability. The two-layer interface is tightly connected by covalent bonds, supporting nutrient exchange and sequential ion diffusion.
[0018] The hydrogel of this invention meets the ISO 10993-5 biocompatibility standard, exhibits no significant cytotoxicity or hematologic toxicity, demonstrates high cell viability, and significantly enhances ALP activity, clearly promoting bone differentiation. Simultaneously, the inner Sr-MOF layer effectively induces macrophage polarization towards the M2 morphology (high Arg-1 expression), downregulates the M1 marker iNOS, and reshapes the immune microenvironment conducive to bone regeneration, providing an effective strategy for addressing chronic inflammation in infectious bone defects. Attached Figure Description
[0019] Figure 1 This is a schematic diagram of the process mechanism of the preparation method of the bilayer composite hydrogel for repairing infectious bone defects according to the present invention; Figure 2 These are scanning electron microscope (SEM) images and physical images of various hydrogel samples from this invention; wherein, Figure 2 (A) is a scanning electron microscope image of Gel1. Figure 2 (B) is a scanning electron microscope image of Gel1@Sr. Figure 2 (C) is a scanning electron microscope image of Gel2. Figure 2 (D) is a scanning electron microscope image of Gel2@CuS. Figure 2 (E) is a photograph of the actual Dual-Gel. Figure 2 (F) is a cross-sectional scanning electron microscope image of the Dual-Gel. Figure 3 Cu in the Dual-Gel of this invention 2+ and Sr 2+ The cumulative release curve; Figure 4 This is a graph showing the DPPH free radical scavenging activity results of five groups of hydrogel samples in this invention; Figure 5 This is a graph showing the blood compatibility and cell viability test results of five groups of hydrogel samples from this invention; among them, Figure 5 (A) shows the results of the hemolysis rate test. Figure 5 (B) shows the results of the cell viability test; Figure 6 This is a graph showing the ALP activity detection results of the bone differentiation-promoting ability of five groups of hydrogel samples in this invention. Figure 7 These are immunofluorescence detection results of five groups of hydrogel samples regulating macrophage polarization according to the present invention; among them, Figure 7 (A) Quantitative analysis of immunofluorescence intensity of the M1 biomarker iNOS. Figure 7 (B) Quantitative analysis of the immunofluorescence intensity of Arg-1, a marker of M2 type. Figure 7 (C) is the polarization ratio diagram of M2 / M1; Figure 8 These are graphs showing the test results of the photothermal and antibacterial properties of five groups of hydrogel samples from this invention; among them, Figure 8 (A) is the photothermal heating curve. Figure 8 (B) shows the inhibition rate against Escherichia coli. Figure 8 (C) shows the inhibition rate against Staphylococcus aureus. Detailed Implementation
[0020] The technical solutions of the invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the invention, not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the invention without creative effort are within the scope of the invention.
[0021] In the description of this invention, it should be noted that the terms "above" and the like indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience and simplification of the description and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this invention.
[0022] In the description of this invention, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance.
[0023] In the description of this invention, it should be noted that, unless otherwise explicitly specified and limited, the terms "connection," "setting," "installation," "fixing," etc., should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal communication between two components. Those skilled in the art can understand the specific meaning of the above terms in this invention according to the specific circumstances.
[0024] like Figure 1 As shown, the first aspect of the present invention provides a method for preparing a bilayer composite hydrogel for repairing infected bone defects, comprising the following steps: S1, Preparation of Strontium-based metal-organic frameworks (Sr-MOF): Weigh 13g of strontium chloride (SrCl2) and 38g of gallic acid (GA), add them to 500mL of deionized water, and magnetically stir for 30min at room temperature to ensure thorough dispersion of the raw materials. Then, add 10mol / L KOH solution dropwise to adjust the pH of the mixture to 8. Transfer the pH-adjusted mixture to a stainless steel reactor with a polytetrafluoroethylene liner, seal it, and place it in a 120℃ oven for 24h. After the reaction, centrifuge the product at 10000rpm for 10min to collect the precipitate, wash it four times with deionized water, and freeze-dry it for 48h to obtain a dark brown cubic Sr-MOF powder, which is then sealed for later use. In this step, the mass ratio of strontium chloride to gallic acid was 13:38, the reaction temperature was 120℃, and the reaction time was 24h.
[0025] S2, Preparation of oxidized sodium alginate (OSA): Dissolve 6g of sodium alginate in 200mL of deionized water and stir in the dark until completely dissolved. Add 5g of sodium periodate under dark conditions and stir at room temperature for 12 hours. After the reaction is complete, transfer the reaction solution to a 3500Da dialysis bag and dialyze with deionized water for 72 hours to remove small molecule impurities. After dialysis, freeze-dry the product to obtain solid oxidized sodium alginate (OSA). In this step, the mass ratio of sodium alginate to sodium periodate is 6:5, the reaction time is 12 hours in the dark, and the dialysis time is 72 hours.
[0026] S3, Preparation of methacrylamide gelatin (GelMA): Gelatin and PBS buffer were dissolved at a mass-to-volume ratio of 1:10 (i.e., 10 mL of PBS buffer per 1 g of gelatin) in a 60°C water bath. After the gelatin was completely dissolved, methacrylic anhydride was added dropwise at a mass ratio of 5:4 to gelatin, and the reaction was carried out at 60°C for 2 hours. After the reaction was completed, 4 times the volume of PBS buffer was added to stop the reaction. The diluted reaction solution was transferred to a dialysis bag and dialyzed against deionized water for one week. After dialysis, the solution was pre-frozen and freeze-dried to obtain methacrylamide gelatin (GelMA) product.
[0027] S4, Preparation of the inner layer hydrogel (Gel1@Sr): A 5% (w / v) aqueous solution of oxidized sodium alginate (OSA), a 5% (w / v) aqueous solution of carboxymethyl chitosan (CMCS), and a 20% (w / v) aqueous solution of gelatin were prepared separately. Equal volumes of the three solutions were mixed, and the Sr-MOF powder prepared in S1 was added to a final concentration of 5 mg / mL. The mixture was ultrasonically dispersed for 15 min to ensure uniform dispersion of Sr-MOF in the mixed solution. After standing for 30 min, the aldehyde groups on the OSA molecular chains reacted with the amino groups on the CMCS and gelatin molecular chains via a Schiff base reaction (-CHO+ -NH2→ -C=N-), forming a cross-linked network. Simultaneously, the gelatin molecular chains formed a physical cross-linked network through chain entanglement at room temperature. Together with the Schiff base chemical cross-linked network, this formed a double-network structure, resulting in the inner hydrogel (Gel1@Sr, where "@" indicates loading, meaning Sr-MOF is loaded in the Gel1 hydrogel matrix).
[0028] It should be noted that after standing for 30 minutes in this step, the inner hydrogel has reached a gel-formed state, maintaining its shape and possessing a certain mechanical strength. However, the Schiff base reaction is a dynamic covalent reaction. After gelation, unreacted aldehyde (-CHO) and amino (-NH2) functional groups remain on the surface and in the shallow region of the inner hydrogel. These residual active functional groups will play a crucial role in the subsequent bilayer composite steps.
[0029] S5, Preparation of the outer layer hydrogel prepolymer (Gel2@CuS): A 5% (w / v) aqueous solution of oxidized sodium alginate (OSA), a 5% (w / v) aqueous solution of carboxymethyl chitosan (CMCS), and a 15% (w / v) aqueous solution of methacrylamide gelatin (GelMA) were prepared. The three solutions were mixed in equal volumes, and 1 wt% of photoinitiator I2959 (i.e., 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone) was added. The mixture was stirred thoroughly until the photoinitiator was completely dissolved. CuS nanoparticles were added to a final concentration of 5 mg / mL, and the mixture was ultrasonically dispersed for 30 min to obtain a homogeneous outer hydrogel prepolymer (Gel2@CuS, i.e., CuS nanoparticles loaded in a Gel2 hydrogel matrix).
[0030] S6, Preparation of Dual-Gel Composite Hydrogel: The outer hydrogel prepolymer solution prepared in step S5 is uniformly coated onto the surface of the inner hydrogel that has been formed in step S4 at a volume ratio of 1:1, ensuring complete coverage and no air bubbles at the interface. Then, irradiation with 365nm ultraviolet light for 5 minutes causes the carbon-carbon double bonds (C=C) on the GelMA molecular chains in the outer hydrogel prepolymer solution to undergo free radical polymerization under the action of photoinitiator I2959, achieving photocrosslinking and curing, forming a chemical crosslinking network of the outer hydrogel. After photocrosslinking, the bilayer hydrogel is allowed to stand for 30 minutes. At this time, the residual aldehyde groups (-CHO) on the surface of the inner hydrogel and the unreacted amino groups (-NH2) on the CMCS molecular chains in the outer hydrogel prepolymer solution continue to undergo Schiff base crosslinking reactions at the interface, forming interlayer covalent bonds. Simultaneously, interlayer van der Waals forces, hydrogen bonds, and other physical interactions synergistically enhance the interfacial bonding strength, resulting in a tightly structured bilayer composite hydrogel (Dual-Gel).
[0031] like Figure 2 As shown in (E), the actual photo of Dual-Gel shows a clear dual-layer structure and a well-integrated interface. Figure 2 (F) is a cross-sectional scanning electron microscope image of Dual-Gel, showing that there is a clear boundary and a tight connection between the outer layer (Gel2@CuS) and the inner layer (Gel1@Sr).
[0032] In summary, the inner layer of the bilayer composite hydrogel of this invention forms a double network structure through the Schiff base reaction of OSA / CMCS / Gel and the entanglement of gelatin molecular chains, while the outer layer forms a double network structure through the Schiff base reaction of OSA / CMCS / GelMA and the photocrosslinking of GelMA. The two layers are covalently connected by interfacial Schiff base bonds, resulting in a stable overall structure.
[0033] The second aspect of the present invention also discloses a bilayer composite hydrogel for repairing infected bone defects, which is prepared by the preparation method of the bilayer composite hydrogel for repairing infected bone defects described in the first aspect.
[0034] This bilayer composite hydrogel comprises an inner hydrogel and an outer hydrogel. The inner hydrogel is a dual-network structure formed by Schiff base crosslinking and gelatin molecular chain entanglement of oxidized sodium alginate, carboxymethyl chitosan, and gelatin, and is loaded with a strontium-based metal-organic framework (Sr-MOF). The outer hydrogel is a dual-network structure formed by Schiff base crosslinking and photocrosslinking of oxidized sodium alginate, carboxymethyl chitosan, and methacrylamide gelatin, and is loaded with copper sulfide (CuS) nanoparticles. The inner and outer hydrogels are covalently linked by interfacial Schiff base bonds. The CuS in the outer hydrogel generates a mild photothermal effect under near-infrared light irradiation, achieving highly efficient and broad-spectrum antibacterial activity. The Sr-MOF in the inner hydrogel continuously releases Sr2+, promoting osteogenic differentiation of BMSCs, scavenging reactive oxygen species, inducing macrophage polarization towards the M2 type, and reshaping the anti-inflammatory immune microenvironment.
[0035] The third aspect of the present invention also discloses the application of a bilayer composite hydrogel in the preparation of bone defect repair materials, wherein the bone defect is an infected bone defect.
[0036] In use, the bilayer composite hydrogel is implanted into the bone defect site, and near-infrared light irradiation is applied after implantation to stimulate the photothermal antibacterial effect of CuS in the outer hydrogel. The preferred near-infrared light wavelength is 808 nm, the preferred power is 1.5 W, and the preferred irradiation time is 5 minutes. The bilayer composite hydrogel achieves early and rapid antibacterial action through the mild photothermal effect of the outer CuS layer, and achieves subsequent immune microenvironment remodeling and osteogenic regeneration through the continuous release of Sr2+ by the inner Sr-MOF layer, thereby meeting the sequential repair needs of infectious bone defects for "early antibacterial action, subsequent immune remodeling, and osteogenic regeneration".
[0037] Comparative Example 1: Preparation and Morphological Characterization of Control Samples: Several control samples were prepared for this comparative example, and their morphology was characterized to compare them with the Dual-Gel bilayer composite hydrogel of this invention. This comparative example includes five sets of parallel samples, denoted as Gel1, Gel1@Sr, Gel2, Gel2@CuS, and Dual-Gel, respectively.
[0038] Control sample 1: Gel1 blank inner layer hydrogel: The same formulation as step S4 was used, but without the addition of Sr-MOF powder. Specifically, 5% (w / v) OSA aqueous solution, 5% (w / v) CMCS aqueous solution, and 20% (w / v) gelatin aqueous solution were prepared separately, mixed in equal volumes, and allowed to stand for 30 min to allow Schiff base cross-linking and molding, resulting in the blank inner layer hydrogel of Gel1. The scanning electron microscope image of Gel1 is shown below. Figure 2 As shown in (A), it can be observed that the Gel1 hydrogel has a continuous porous structure, exhibiting loose pores and large pore size.
[0039] Control sample 2: Gel1@Sr monolayer strontium-loaded hydrogel: That is, the sample prepared in step S4. The scanning electron microscope image of Gel1@Sr is shown below. Figure 2 As shown in (B), it also has a continuous porous structure. Due to the successful loading of Sr-MOF, the pore size of Gel1@Sr is smaller than that of Gel1, presenting a dense honeycomb porous structure, indicating that Sr-MOF is uniformly dispersed in the hydrogel matrix and plays a regulatory role in the pore structure.
[0040] Control sample 3: Gel2 blank outer hydrogel: The same formulation as step S5 was used, but without the addition of CuS nanoparticles. Specifically, 5% (w / v) OSA aqueous solution, 5% (w / v) CMCS aqueous solution, and 15% (w / v) GelMA aqueous solution were prepared, mixed in equal volumes, and 1 wt% photoinitiator I2959 was added. The mixture was then cured by irradiation with 365 nm UV light for 5 min to obtain the blank outer hydrogel of Gel2. The scanning electron microscope image of Gel2 is shown below. Figure 2 As shown in (C), it has a porous structure with a large pore size.
[0041] Control sample 4: Gel2@CuS monolayer copper-loaded hydrogel: This refers to the monolayer sample obtained after curing in step S5. The scanning electron microscope image of Gel2@CuS is shown below. Figure 2 As shown in (D), CuS particles are uniformly distributed in Gel2@CuS, and the hydrogel still maintains a porous structure.
[0042] Experimental sample: Dual-Gel bilayer composite hydrogel That is, the finished product obtained in step S6. Figure 2 (E) is a photograph of the Dual-Gel, showing a clear dual-layer structure and a well-integrated interface; Figure 2 (F) is a cross-sectional SEM image of Dual-Gel, which shows that there is a clear boundary between the outer layer (Gel2@CuS) and the inner layer (Gel1@Sr) and they are tightly connected, with no peeling or gaps between the layers.
[0043] Performance testing: Ion release behavior test: Dual-Gel bilayer hydrogels were immersed under physiological conditions (phosphate-buffered saline, PBS, pH 7.4, 37℃). Supernatants were collected on days 3, 7, 10, and 14, and Cu was detected by inductively coupled plasma mass spectrometry (ICP-MS). 2+ and Sr 2+ The cumulative release concentration.
[0044] Test results are as follows Figure 3 As shown. On the 3rd day, Cu 2+ Approximately 55% has been released cumulatively, Sr 2+ The cumulative release was approximately 20%; as the soaking time increased, the cumulative release of both ions gradually increased, reaching a certain level by day 14, with Cu... 2+ and Sr 2+ The cumulative release of CuS in both layers exceeded 90%. The results showed that CuS in the outer hydrogel was released rapidly in the early stages of implantation, which facilitated its rapid antibacterial effect; while Sr-MOF in the inner hydrogel exhibited a slow and continuous release characteristic, which was beneficial for its sustained osteogenic and immunomodulatory functions in the later stages of repair. The Dual-Gel composite hydrogel, in the early stages of repair, primarily released CuS... 2+Primarily focused on releasing Sr, with continued release in the later stages. 2+ It achieves sequential ion release, which matches the sequential repair needs of infected bone defects, namely "early antibacterial and later osteogenesis".
[0045] Antioxidant performance test: The antioxidant activity of each hydrogel group was evaluated using the DPPH (1,1-diphenyl-2-picrylhydrazine) free radical scavenging method. Five hydrogel samples (Gel1, Gel1@Sr, Gel2, Gel2@CuS, Dual-Gel) were reacted with DPPH solution in the dark, and the change in absorbance at 517 nm was measured to calculate the DPPH free radical scavenging rate.
[0046] Test results are as follows Figure 4 As shown, Gel1@Sr and Dual-Gel achieved a DPPH radical scavenging rate of approximately 80%, significantly higher than Gel1 (approximately 39%), Gel2 (approximately 29%), and Gel2@CuS (approximately 38%). These results indicate that the inner Sr-MOF layer endows the hydrogel with excellent antioxidant capacity. Sr-MOF effectively scavenges reactive oxygen species by mimicking the enzyme-like activities of superoxide dismutase (SOD) and catalase (CAT), which is beneficial for improving the oxidative stress microenvironment at sites of infectious bone defects.
[0047] Blood compatibility and cell viability test: Blood compatibility test (hemolysis test): Five groups of hydrogel samples were co-incubated with diluted rabbit red blood cell suspension. PBS was used as the negative control group (0% hemolysis) and deionized water was used as the positive control group (100% hemolysis). The hemolysis rate was calculated by measuring the absorbance of the supernatant at 540 nm.
[0048] Hemolysis test results as follows Figure 5 As shown in (A), the hemolysis rate of all five groups of hydrogels was less than 5%, which was not significantly different from the negative control group (PBS). This indicates that the hydrogel of the present invention has good blood compatibility and meets the requirements of ISO 10993-5 biocompatibility standard for hemolysis rate (<5%) of medical materials.
[0049] Cell viability assay (CCK-8 assay): Bone marrow mesenchymal stem cells (BMSCs) were co-cultured with hydrogels from each group. CCK-8 reagent was added at 1, 3 and 5 days of culture, and absorbance at 450 nm was measured to assess cell viability.
[0050] Cell viability results as follows Figure 5As shown in (B), the cell viability of the Gel1@Sr and Dual-Gel groups increased significantly over time, and was significantly higher than that of the Gel1, Gel2 and Gel2@CuS groups, indicating that Sr-MOF can continuously release Sr. 2+ It promotes the proliferation of BMSCs. This result further confirms that Sr-MOF has a proliferative effect on BMSCs, which is beneficial to cell recruitment and tissue regeneration during bone defect repair.
[0051] Osteogenesis Promotion Capacity Assay: BMSCs were co-cultured with hydrogels from each group, and the osteoogenesis promotion capacity of each hydrogel was assessed by detecting alkaline phosphatase (ALP) activity. After 7 days of culture, cells were lysed and proteins were collected. ALP activity was detected using an ALP kit, and the total protein content was determined by the BCA method for correction.
[0052] Test results as follows Figure 6 As shown, the ALP activity of the Gel1@Sr and Dual-Gel groups was significantly higher than that of the Gel1, Gel2, and Gel2@CuS groups. The ALP activity of the Gel1@Sr group was approximately 2-3 times that of the Gel1 group, while the Dual-Gel group was comparable to that of the Gel1@Sr group. These results indicate that the inner Sr-MOF can sustainably release Sr. 2+ It effectively promotes early osteogenic differentiation of BMSCs, and the dual-layer composite structure (Dual-Gel) does not weaken the osteogenic effect of Sr-MOF. The photothermal function of the outer CuS layer and the osteogenic function of the inner Sr-MOF layer do not interfere with each other, and can achieve functional synergy.
[0053] Immunomodulatory performance test: RAW264.7 macrophages were co-cultured with hydrogel extracts from each group. The expression of the M1 marker inducible nitric oxide synthase (iNOS) and the M2 marker arginase-1 (Arg-1) was detected by immunofluorescence staining to evaluate the regulatory ability of each hydrogel on macrophage polarization.
[0054] Immunofluorescence detection results as follows Figure 7 As shown. Figure 7 (A) shows the quantitative analysis of immunofluorescence intensity of iNOS (M1 type marker). The results show that the expression of iNOS in the Gel2@CuS group is higher, indicating that the outer CuS can promote macrophage polarization to M1 type, which is beneficial to the activation of early antibacterial immune response. Figure 7 (B) shows the quantitative analysis of the immunofluorescence intensity of Arg-1 (M2 type marker). The results show that Arg-1 expression in the Gel1@Sr group is significantly increased, indicating that the inner Sr-MOF can effectively induce macrophages to polarize to the M2 type. Figure 7(C) shows the M2 / M1 polarization ratio. The M2 / M1 polarization ratio of the Dual-Gel group was significantly higher than that of other control groups, indicating that the bilayer composite hydrogel effectively induced macrophages to M2 polarization through the dominant role of the inner Sr-MOF, remodeled the anti-inflammatory immune microenvironment, and provided favorable immune conditions for bone regeneration.
[0055] Photothermal and antibacterial performance tests: Photothermal performance test: Under the irradiation of near-infrared light (NIR, wavelength 808nm) with a power of 1.5W, the temperature change of each group of hydrogels was recorded using an infrared thermal imager.
[0056] Photothermal heating results are as follows Figure 8 As shown in (A), Gel2@CuS and Dual-Gel reached a temperature of 42-45℃ within 5 minutes under NIR irradiation, reaching a mild photothermal therapy window (42-45℃ can effectively kill bacteria and avoid thermal damage to surrounding normal tissues), while Gel2 (without CuS) did not heat up, indicating that the CuS nanoparticles loaded in the outer hydrogel endow Dual-Gel with excellent photothermal conversion performance.
[0057] Antibacterial performance test: The antibacterial performance of each group of hydrogels against Escherichia coli and Staphylococcus aureus was evaluated using the plate coating method. Each group of hydrogels was co-cultured with bacterial suspensions (some samples were irradiated with NIR), plated on agar plates, and the number of colonies was counted to calculate the inhibition rate.
[0058] Antibacterial results such as Figure 8 (B) (E. coli) and Figure 8 (C) (Staphylococcus aureus) is shown. Under NIR irradiation, the Gel2@CuS+NIR and Dual-Gel+NIR groups showed extremely low colony counts and inhibition rates >90%. Without NIR irradiation, Gel2@CuS and Dual-Gel also exhibited certain Cu inhibition. 2+ Chemical antibacterial activity was observed, but the antibacterial effect was significantly lower than that of the NIR irradiation group. The results indicate that Dual-Gel combined with NIR irradiation provides highly efficient and broad-spectrum antibacterial activity, which is attributed to the mild photothermal effect generated by the outer CuS layer under NIR irradiation and the Cu... 2+ The synergistic effect of its own chemical antibacterial activity.
[0059] In summary, this invention addresses the sequential requirements of "early antibacterial treatment, subsequent immune remodeling, and osteogenic regeneration" in the repair of infected bone defects, and successfully constructs a functionally partitioned bilayer composite hydrogel (Dual-Gel). Through comparative verification with the aforementioned control samples, the technical effects of this hydrogel can be summarized as follows: Synergistic temporal function: In the early stages of implantation, near-infrared light irradiation is used to generate a mild photothermal effect (42-45℃) in the outer CuS layer, achieving highly efficient broad-spectrum antibacterial activity (antibacterial inhibition rate >90%), rapidly eliminating pathogens and controlling the spread of infection; the inner Sr-MOF layer continuously releases Sr²⁺, which intermittently promotes osteogenic differentiation of BMSCs (significantly increases ALP activity), eliminates reactive oxygen species (DPPH clearance rate of about 80%), and induces macrophages to polarize towards the M2 type (significantly increases the M2 / M1 ratio) in the later stages, constructing an anti-inflammatory immune microenvironment, and precisely simulating the natural process of bone repair "antibacterial first, then osteogenic".
[0060] Material synergy and structural adaptation: Sr-MOF not only continuously releases strontium to promote bone formation, but also scavenge reactive oxygen species by mimicking the enzyme-like activities of superoxide dismutase and catalase, thus exerting antioxidant and immunomodulatory functions; CuS achieves highly efficient photothermal antibacterial activity under near-infrared light, while simultaneously releasing Cu 2+ Promotes angiogenesis. The inner layer forms a double network structure through Schiff base reaction and molecular entanglement, while the outer layer combines Schiff base reaction and photocrosslinking to give the hydrogel excellent shape adaptability. The two-layer interface is tightly connected by covalent bonds, supporting nutrient exchange and sequential ion diffusion.
[0061] Outstanding biocompatibility and immunomodulatory capabilities: The hydrogel of this invention meets the ISO 10993-5 biocompatibility standard, exhibits no significant cytotoxicity or hemotoxicity (hemolysis rate <5%), demonstrates high cell viability, and significantly enhances ALP activity, clearly promoting bone differentiation. Simultaneously, the inner Sr-MOF layer effectively induces macrophage polarization towards the M2 type (high Arg-1 expression), downregulates the M1 marker iNOS, and reshapes the immune microenvironment conducive to bone regeneration.
[0062] In summary, this bilayer composite hydrogel possesses excellent long-term drug release capacity, biocompatibility, immunomodulatory capacity, and antibacterial capacity, providing a novel strategy for the integrated treatment of infectious bone defects and showing significant clinical translational potential in the field of biomedical materials.
[0063] It is understood that the above embodiments are merely exemplary implementations used to illustrate the principles of the present invention, and the present invention is not limited thereto. For those skilled in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.
Claims
1. A method for preparing a bilayer composite hydrogel for repairing infected bone defects, characterized in that, Includes the following steps: S1, preparation of strontium-based metal-organic frameworks; S2, to prepare sodium alginate oxide; S3, preparation of methacrylamide gelatin; S4, the sodium alginate oxide, carboxymethyl chitosan and gelatin are mixed, and the strontium-based metal-organic framework is added, and cross-linked to obtain the inner hydrogel; the strontium-based metal-organic framework is prepared by hydrothermal reaction of strontium chloride and gallic acid under alkaline conditions; S5, the sodium alginate oxide, carboxymethyl chitosan, methacrylamide gelatin and copper sulfide nanoparticles are mixed to obtain the outer hydrogel prepolymer solution; S6, the outer layer hydrogel prepolymer is applied to the surface of the inner layer hydrogel, the outer layer is cured by photocrosslinking, and then left to stand to allow interfacial crosslinking to occur between the layers, thus obtaining a bilayer composite hydrogel.
2. The method for preparing the bilayer composite hydrogel for repairing infected bone defects according to claim 1, characterized in that, The oxidized sodium alginate is prepared by an oxidation reaction between sodium alginate and sodium periodate.
3. The method for preparing the bilayer composite hydrogel for repairing infected bone defects according to claim 1, characterized in that, The methacrylated gelatin is prepared by acylation reaction of gelatin and methacrylic anhydride.
4. The method for preparing the bilayer composite hydrogel for repairing infected bone defects according to claim 1, characterized in that, In step S4, the mass-volume concentrations of sodium alginate, carboxymethyl chitosan, and gelatin are 5%, 5%, and 20%, respectively, and the amount of strontium-based metal-organic framework added is 5 mg / mL.
5. The method for preparing the bilayer composite hydrogel for repairing infected bone defects according to claim 1, characterized in that, In step S5, the mass-volume concentrations of sodium alginate, carboxymethyl chitosan, and methacrylamide gelatin are 5%, 5%, and 15%, respectively. The amount of copper sulfide nanoparticles added is 5 mg / mL. The outer hydrogel prepolymer also contains 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone.
6. The method for preparing the bilayer composite hydrogel for repairing infected bone defects according to claim 1, characterized in that, In step S6, the photocrosslinking is performed by ultraviolet light irradiation for 5 minutes.
7. A bilayer composite hydrogel for repairing infected bone defects, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 6.
8. The application of a bilayer composite hydrogel for repairing infected bone defects as described in claim 7 in the preparation of bone defect repair materials, characterized in that, The bone defect is an infected bone defect.
9. The application of the bilayer composite hydrogel for repairing infected bone defects according to claim 8 in the preparation of bone defect repair materials, characterized in that, When the bilayer composite hydrogel is used for bone defect repair, it is combined with near-infrared light irradiation after implantation to stimulate the photothermal antibacterial effect of the outer hydrogel.
Citation Information
Patent Citations
Preparing method for infrared response high-strength hydrogel for cartilago articularis repair
CN105107019A
Double-metal MOF hydrogel dressing for promoting wound healing as well as preparation method and application of double-metal MOF hydrogel dressing
CN117258028A